Quantum leap forward in understanding biological processes. (Research'eu results magazine)
EU-funded researchers have successfully applied quantum physics in order to better understand some fundamental biological processes. This ground breaking work could eventually help industry to develop more efficient light harvesting technologies and artificial odour sensors.